TEKNOLOGI PEMBELAJARAN: MENUJU PEMBELAJARAN MULTI SUMBER - Laila Nursafitri (LPPM STAI DARUSSALAM LAMPUNG, 2014)
The instructional is a series of interrelated components to achieve the goal oflearning. The component of instructional is students, the materials, methods,learning resources, teachers, and the environment are interconnected anddependence to one another. As a component of the instructional process, thelearning resources play an important role in the learning success.Instructional technologyis an applied discipline, which developed becauseof the needs in the field,need to learn, learn more effectively, more efficiently,wider, and faster.Instructional technologyto facilitate the learning throughtheory and practice in the design, development, utilization, management,and evaluation of processes and resources for learning.Various learning resources are developed now makes it easy for learnersto learn.Learners are no longer dependent on teachers. Through a multisource learning learners are required to behave in an honest and able todevelop independence in learning